These are all of the same type.

$\displaystyle 8x - 7 =5(x + 4)$

$\displaystyle 8x - 7 = 5 \cdot x + 5 \cdot 4$

$\displaystyle 8x - 7 = 5x + 20$

$\displaystyle 8x - 7 - 5x = 5x + 20 - 5x$

$\displaystyle 3x - 7 = 20$

$\displaystyle 3x - 7 + 7 = 20 + 7$

$\displaystyle 3x = 27$

$\displaystyle \frac{3x}{3} = \frac{27}{3}$

$\displaystyle x = 9$

The other three use the same basic pattern of solution. Try them again, step by step, using the above solution as a model. If you are still stuck on any of them, just let us know.

-Dan